The usefulness of plateletcrit to predict cardiac syndrome X in patients with normal coronary angiogram - Oylumlu, Muhammed; Oylumlu, Mustafa; Yuksel, Murat; Dogan, Adnan; Cakici, Musa; Ozgeyik, Mehmet; Yildiz, Abdulkadir; Kilit, Celal; Amasyali, Basri (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Cardiac syndrome X (CSX) is a clinical entity defined as the triad of typical angina pectoris on exercise, electrocardiographic or metabolic findings of ischemia and normal epicardial coronary arteries. Platelets, whose amount in the blood is indicated with plateletcrit (PCT), play an important role in inflammatory and thrombotic processes and the physiopathology of cardiovascular events. Aim : To investigate the association between cardiac syndrome X and PCT and platelet count. Material and methods : A total of 113 patients with normal coronary angiogram were included in the study. Fifty patients with typical chest pain and evidence of myocardial ischemia in non-invasive tests formed the CSX patient group. The control group consisted of 63 age- and gender-matched patients with normal coronary arteries but without angina. Results : The mean PCT value of the CSX group was significantly higher than that of the control group (0.22 ±0.06 vs. 0.19 ±0.04; respectively, p = 0.03). Higher PCT was found to be associated with the presence of CSX in patients with normal coronary arteries by multivariate logistic regression analysis. Conclusions : We suggest that high PCT may predict the presence of cardiac syndrome X in patients with normal coronary arteries. The value of PCT appears additive to conventional expensive methods commonly used in CSX prediction.